2020
DOI: 10.1002/cpa.21923
|View full text |Cite
|
Sign up to set email alerts
|

Continued Fractions and Hankel Determinants from Hyperelliptic Curves

Abstract: Following van der Poorten, we consider a family of nonlinear maps that are generated from the continued fraction expansion of a function on a hyperelliptic curve of genus g. Using the connection with the classical theory of J -fractions and orthogonal polynomials, we show that in the simplest case g D 1 this provides a straightforward derivation of Hankel determinant formulae for the terms of a general Somos-4 sequence, which were found in a particular form by Chang, Hu, and Xin. We extend these formulae to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(49 citation statements)
references
References 54 publications
(72 reference statements)
2
47
0
Order By: Relevance
“…for all n ∈ Z, which (up to squaring one of the variables) is just the infinite Toda lattice written in Flaschka coordinates. Thus the simultaneous solutions of the map and the Hamiltonian flow provide genus 1 solutions of the Toda lattice, and for genus g > 1 an analogous statement holds for the other maps constructed in [12]; further details will be presented elsewhere. = nx n and overall scale, the third independent shadow solution of Somos-4 can be obtained from the associated solution of the map (3.4), in the form…”
Section: Solution Of Linear Difference Equationmentioning
confidence: 67%
See 4 more Smart Citations
“…for all n ∈ Z, which (up to squaring one of the variables) is just the infinite Toda lattice written in Flaschka coordinates. Thus the simultaneous solutions of the map and the Hamiltonian flow provide genus 1 solutions of the Toda lattice, and for genus g > 1 an analogous statement holds for the other maps constructed in [12]; further details will be presented elsewhere. = nx n and overall scale, the third independent shadow solution of Somos-4 can be obtained from the associated solution of the map (3.4), in the form…”
Section: Solution Of Linear Difference Equationmentioning
confidence: 67%
“…It was conjectured by Barry and proved by various authors that certain Somos-4 sequences could be expressed as Hankel determinants [1,2,29]. In [12] we showed that these results can be unified and further generalized by applying van der Poorten's work on Jacobi continued fractions (J-fractions) in hyperelliptic function fields [24]. In the genus 1 case, one expands a certain function G on a quartic curve as a J-fraction, that is…”
Section: Hankel Determinant Formulaementioning
confidence: 76%
See 3 more Smart Citations